Enhancement of the Josephson current by magnetic field in superconducting tunnel structures with a paramagnetic spacer - Krivoruchko, V.N.; Koshina, E.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The dc Josephson critical current of a (S/M)IS tunnel structure in a parallel magnetic field is investigated (here S is a superconductor, S/M is a proximity-coupled S and paramagnetic metal M bilayer, and I is an insulating barrier). We consider the case when, due to Hund`s rule, in the metal M the effective molecular interaction aligns the spins of the conduction electrons antiparallel to the localized spins of magnetic ions. It is predicted that for the tunnel structures under consideration there are conditions such that the destructive action of the internal and the applied magnetic fields on Cooper pairs is weakened, and increase of the applied magnetic field causes field-induced enhancement of the critical tunnel current. The experimental realization of this interesting effect of the interplay between superconductivity and magnetism is also discussed.